Fourth Hankel and Toeplitz Determinants for Reciprocal of Bounded Turning Functions and Inverse of Reciprocal of Bounded Turning Functions Subordinate to cos \(z\) - Yakaiah, K.; Sharma, R. Bharavi; Kumar, V. Suman; Sambasivarao, S. (Communications in Mathematics and Applications, 2023)
The purpose of the present research article is to find an upper bounds of fourth Hankel and Toeplitz determinants for reciprocal of bounded turning functions subordinate to cos \(z\) and for the inverse of reciprocal of bounded turning functions subordinate to cos \(z\). The Zalcman conjecture is verified for specific values of \(n\) for the functions in these classes. The sharp upper bounds for Fekete-Szegö inequalities were obtained.